PENGARUH ARSITEKTUR ERA MAJAPAHIT PADA PENINGGALAN ARSITEKTUR ISLAM DI BANTEN DITINJAU BERDASARKAN TATA RUANG, SOSOK, DAN ORNAMEN - Gilbert Aldo T.; Rahadhian Prajudi H. (Riset Arsitektur (RISA), 2024)
Abstract - The Sultanate of Banten was one of the starting points for the spread of Islam in Java. Its location on the North Coast and its close relationship with Pasundan and Cirebon open up opportunities for influence from various parties to enter Banten. Given that the Sultanate of Banten (Islamic in nature) was established in the era of the Hindu-Buddhist transition to Islam in Java, it is possible that there is still Hindu-Buddhist influence, especially Majapahit as the last major empire that existed before Islam in Banten civilization, especially in terms of architecture and urban planning. This study discusses descriptive and qualitatively how the architectural elements in the heritage of Islamic architecture in Banten are influenced by the architecture of the Majapahit era and which were brought indirectly by Cirebon. The analysis carried out is based on spatial planning, figures, and ornaments as benchmarks that can be seen physically on the existing relics. Objects in Banten will be aligned with comparison objects from Majapahit, Cirebon, and also the Sendang Duwur Mosque complex. The results of the study indicate that the influence of Majapahit is still legible in Banten. This shows the syncretism that occurs between Hinduism and Islam, Sundanese and Javanese. This research is limited to the presence or absence of Majapahit elements in Banten architecture, so further research is needed to examine the interpretation of meaning and architectural evolution that occurs between figure and ornament, the proportion of Majapahit attributes to Banten. Keywords: Transition, Majapahit, Influence, Architecture, Islam, Banten